Integrasi Nilai-Nilai Islam dalam Pendidikan Inklusif: Telaah Pemikiran Muhammad Abduh tentang Pendidikan Modern - Dede Kusnadi; Jaenal Abidin; Mulyana; Aldi Rahman Dirta (CV. Creative Tugu Pena, 2025)
Inclusive education in the contemporary era presents both challenges and opportunities to establish a just and equitable educational framework for all students, devoid of discrimination. The objective of this research is to analyse the incorporation of Islamic values within inclusive education, drawing upon Muhammad Abduh's perspectives on modern education. This study employs a qualitative methodology, utilising a literature review approach to delve into Abduh's ideas through an examination of his works and relevant literature pertaining to Islamic education. The findings indicate that Abduh advocates for an educational paradigm grounded in universal Islamic values, such as justice, tolerance, and rahmatan lil 'alamin, which resonate with the principles of inclusive education. He underscores the necessity of harmonising religious teachings with scientific inquiry, as well as the implementation of flexible pedagogical methods to cater to the diverse needs of students. These values are deemed capable of fostering an adaptive learning environment and facilitating the inclusion of all children, including those with special needs. The implications of this research suggest that the integration of Islamic values into inclusive education may serve as an effective strategy in addressing global challenges, whilst also nurturing a generation equipped with both intellectual and moral acumen. Consequently, Muhammad Abduh's insights significantly contribute to the realisation of an education system that is inclusive, humanistic, and attuned to the demands of contemporary society.